Membangun Efikasi Diri Karyawan Hotel di Era Transformasi Digital AI - Olivia Risqhika Firdyaningtyas; Aletta Dewi Maria Th (Pusat Riset dan Inovasi Nasional, 2025)
The rise of artificial intelligence (AI)-driven digital transformation in the hospitality industry presents challenges for employees in maintaining relevance and work effectiveness. This study aims to understand how hotel employees develop self-efficacy in adapting to AI implementation. Using a qualitative interpretivist approach and a multi-site phenomenological case study design, the research was conducted at Hotel Neo Candi Semarang involving nine informants from various departments. Data were collected through semi-structured interviews, participant observation, and document analysis, then examined using a six-phase thematic analysis. Findings reveal that employees’ self-efficacy evolves through three layered stages: basic (confidence to try), operational (confidence in routine use), and adaptive (confidence to innovate and solve problems). Employees conceptualize AI as a “work partner” within Indonesia’s cultural context emphasizing harmony and collectivism. Five key factors shape self-efficacy development: systematic organizational support, user-friendly technology, collaborative learning culture, progressive mastery experiences, and task relevance. High self-efficacy is positively associated with job performance, satisfaction, and problem-solving capability, highlighting the importance of human-centered strategies in AI adoption within the hospitality sector.